Zachycovaní emisí CO2 z průmyslových zdrojů - Wichterlová, Jana; Roubíček, Václav; Pánek, Petr (Chemické listy, 2008)
Carbon dioxide capture and storage (CCS) is considered as one of the options for reducing CO2 emissions. CCS can be applied to large point sources of CO2, such as power plants and in large industrial processes. The CO2 capture is to produce a concentrated stream of highpressure CO2. The capture systems typically employ absorption of CO2 from flue gases with CO2 concentration up to 15 %. The oxygen-fuel systems use oxygen instead of air for fuel combustion to produce mainly water vapour and CO2 (more than 80 %); the water vapour is easily removed by cooling. In precombustion capture, the fuel is converted to CO2 (15-60 %) and H2 at high pressure; then CO2 is separated by adsorption or absorption. The emerging capture technologies require development of largescale membrane separation processes, novel absorption solvents and sorbents, membrane-absorbent systems, hightemperature oxygen transport membranes for oxygen production, oxyfuelling via chemical looping, combined reaction/ separation systems and new high-temperature materials.
Keywords: Adsorption; financování organizované; Industrial Waste; Financing, Organized; látky znečišťující vzduch; Air Pollutants; adsorpce; oxid uhličitý; průmyslový odpad; Carbon Dioxide